Strategi Pengembangan Rantai Pasok Berbasis Sistem Kendali Internal pada Produksi Beras Organik - Hakim, Shofia Nurul; Nazli, Rizal Syarief Sjaiful; Palupi, Nurheni Sri (Institut Pertanian Bogor, 2018)
The high demand for organic rice on the market indicates that the organic rice business has good potential and opportunities to be developed, so as to encourage organic agriculture to become competitive and sustainable. This is an opportunity for farmers, especially farmers who are under CV. Sirtanio Organic Indonesia is expected to provide high value added to its member farmers, so as to boost the economy of farmers towards prosperity. The purpose of this study are: (1) Assessing the simple feasibility of organic rice farming based on Internal Control System (ICS) organic farming in the company is seen from the financial aspect; (2) Describe and analyze the characteristics of organic rice products in supply chains based on ICS in organic farming; and (3) Formulate supply chain strategies for organic rice based ICS agricultural products. The analytical method used is business feasibility analysis which is then identified internal and external factors which are then accumulated using SWOT and formulated several strategies using QSPM. The conclusion of the research results are: (1) The advantage is quite good (>1), the analysis of the R/C ratio calculation for organic rice farming for farmers and companies, namely farmers (2.25) and CV Sirtanio (1.56); (2) Organic certification is an internal force with the opportunity to offer export market share that is quite open, so that it is obtained a ICS -based supply chain development strategy, namely: (a) Development of collaboration with online-shop (score 5,895); (b) Strengthening ICS-based supply chain functions through the implementation of internal audits conducted by the ICS team (score 5,671); and (c) Maintained the organic farming system based on the agreed ICS according to the rules of SNI 6729: 2016 (score 5,541).